2003
DOI: 10.1111/j.1754-4505.2003.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine and xylitol gum in caries prevention

Abstract: This paper presents the current best evidence on the respective and comparative outcomes of chlorhexidine and xylitol and extrapolates these data to individuals with special needs. It analyzes the probable mechanisms of action for both chlorhexidine and xylitol then reviews individual products and discusses the anticipated effectiveness of these products in individuals with special needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
2
8
0
7
Order By: Relevance
“…4,10,[26][27][28][29]31 However, xylitol also reduces both biofilm and S. mutans levels when added to a patients' diet as a sweetener, thus preventing early development of caries. 11,13,32,33 The results found in the present study corroborate these findings, since groups G1 (XYL) and G2 (CHX + XYL) showed enhanced reduction in biofilm levels in the sixth month compared to other groups (p <0.05).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…4,10,[26][27][28][29]31 However, xylitol also reduces both biofilm and S. mutans levels when added to a patients' diet as a sweetener, thus preventing early development of caries. 11,13,32,33 The results found in the present study corroborate these findings, since groups G1 (XYL) and G2 (CHX + XYL) showed enhanced reduction in biofilm levels in the sixth month compared to other groups (p <0.05).…”
Section: Discussionsupporting
confidence: 88%
“…4,6,8,11,26 At low concentrations, chlorhexidine can be considered a bacteriostatic agent 3 because it affects the metabolic activity of microorganisms by acting on cell membranes, causing intracellular disruption. 27 However, at high concentrations, this product seems to affect the cellular content, thus being bactericidal.…”
Section: Discussionmentioning
confidence: 99%
“…O controle da cárie dentária e da doença periodontal, ainda nos dias de hoje, é um desafio a ser alcançado pela Odontologia. Alguns estudos têm demonstrado que uma das formas mais eficazes de se prevenir tais doenças é por meio da remoção mecânica do biofilme bacteriano encontrado sobre a superfície dos dentes, a qual pode ser realizada com a utilização de escovas dentais, fio dental ou pela profilaxia profissional (LÖE;SILNESS 1963;ANDERSON 2003;FEJERSKOV;KIDD, 2005;KUMAR;GREEN, 2005).…”
Section: Introductionunclassified
“…Os métodos mecânicos para limpeza dentária devem ser a escolha antes da utilização de qualquer tipo de agente químico para o controle rotineiro do biofilme dentário. O controle químico do biofilme dentário deverá ser empregado de forma suplementar, quando o controle mecânico, no sentido de evitar o acúmulo de bactérias sobre os dentes, não puder ser realizado diariamente ou estiver inadequado (ANDERSON, 2003;BOZKURT et al, 2005;PARASKEVAS, 2005;LAING et al, 2008).…”
Section: Introductionunclassified
“…A number of observational studies and clinical trials have shown the caries-protective effect of xylitol, and to a lesser extent sorbitol (Honkala et al 2006, Burt 2006, Anderson 2003, Hayes 2001. For the first time, comprehensive Finnish "Turku Sugar Study" (Scheinin et al 1976) revealed an 85% decline in dental caries by total dietary substitution of sucrose with xylitol over a 2-year period.…”
Section: Non-cariogenic Sweetenersmentioning
confidence: 99%